The Effect of Using Special Gloves on the Accuracy of Volleyball Slamming and Smashing Skills - Assistant Professor Diana Hussein Abdul Karim (Proximus Journal Publishing, 2025)
It is well known that the skills of setting up and smashing can be developed in several ways and means, whether these means are educational or training. Hence, the idea of research crystallized using some training methods with special gloves to develop the accuracy of the skills of setting up and smashing, which constitute the team's contribution in responding to the dominance of the opposing team and preparing for the attack to carry out crushing blows. Hence, the importance of researching the effect of using special gloves on the accuracy of the skills of setting up and smashing. the opposing team and preparing for the attack to perform smashes. Hence, the importance of the research on the effect of using special gloves on the accuracy of serving and smashing skills in volleyball. Through her observations and experience in the field of sports and her work in the physical education department, the researcher noticed a decline in the level of skill accuracy among the college team, especially in the skills of setting and spiking, and a failure to achieve the best and ideal attack during play. This prompted the researcher to try to identify the effect of using special gloves on improving the level of performance in setting and spiking skills in volleyball.
Keywords: Special gloves; Setting skill; Volleyball